I Have Seen Sine, Cosine, What About Tangent?

Geometry Level 5

Suppose a , b , c a, b, c are sides of a triangle Δ A B C \Delta ABC and the roots of the following equation. x 3 24 x 2 + 180 x 420 = 0. x^3-24x^2+180x-420=0. If tan A + tan B + tan C = p q \tan A+\tan B+\tan C=-\dfrac{p}{q} , where p p and q q are coprime positive integers , find the value of p + q p+q .


Inspiration .


The answer is 889.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chew-Seong Cheong
Jul 19, 2016

Relevant wiki: Solving Triangles - Problem Solving - Hard

By Vieta's formula : { a + b + c = 24 a b + b c + c a = 180 a b c = 420 \begin{cases} a+b+c = 24 \\ ab+bc+ca = 180 \\ abc = 420 \end{cases}

By sine rule : sin A a = sin B b = sin C c = k { sin A = k a sin B = k b sin C = k c \dfrac {\sin A}a = \dfrac {\sin B}b = \dfrac {\sin C}c = k \implies \begin{cases} \sin A = ka \\ \sin B = kb \\ \sin C = kc \end{cases}

By Heron's formula :

A = s ( s a ) ( s b ) ( s c ) where s = a + b + c 2 = 12 = 12 ( 1 2 3 24 ( 12 ) 2 + 180 ( 12 ) 420 ) Note that ( x a ) ( x b ) ( x c ) = x 3 24 x 2 + 180 x 420 = 12 ( 12 ) = 12 \begin{aligned} A_\triangle & = \sqrt{\color{#3D99F6}{s}(\color{#3D99F6}{s}-a)(\color{#3D99F6}{s}-b)(\color{#3D99F6}{s}-c)} & \small \color{#3D99F6}{\text{where }s = \frac {a+b+c}2 = 12} \\ & = \sqrt{12\color{#3D99F6}{(12^3-24(12)^2+ 180(12)-420)}} & \small \color{#3D99F6}{\text{Note that } (x-a)(x-b)(x-c) = x^3-24x^2+ 180x-420} \\ & = \sqrt{12\color{#3D99F6}{(12)}} \\ & = 12 \end{aligned}

But A = 1 2 a b sin C = 1 2 a b c k a b c k = 24 A_\triangle = \frac 12 ab \sin C = \frac 12 abck \implies abck = 24

By cosine rule :

a 2 = b 2 + c 2 2 b c cos A cos A = b 2 + c 2 a 2 2 b c = a 2 + b 2 + c 2 2 a 2 2 b c See Note = 216 2 a 2 2 b c = 108 a 2 b c \begin{aligned} a^2 & = b^2 + c^2 - 2bc \cos A \\ \implies \cos A & = \frac {b^2 + c^2 - a^2}{2bc} \\ & = \frac {\color{#3D99F6}{a^2 + b^2 + c^2} - 2a^2}{2bc} & \small \color{#3D99F6}{\text{See Note}} \\ & = \frac {\color{#3D99F6}{216} - 2a^2}{2bc} \\ & = \frac {108 - a^2}{bc} \end{aligned}

Now, we have:

tan A + tan B + tan C = tan A tan B tan C A + B + C = 18 0 tan A tan B tan C = p q q p = cot A cot B cot C = cos A cos B cos C sin A sin B sin C = 108 a 2 b c k a 108 b 2 c a k b 108 c 2 a b k c = 10 8 3 10 8 2 ( a 2 + b 2 + c 2 ) + 108 ( ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ) ( a b c ) 2 ( a b c k ) 3 See Note = 114192 13824 = 793 96 \begin{aligned} \tan A + \tan B + \tan C & = \tan A \tan B \tan C & \small \color{#3D99F6}{A+B+C = 180^\circ} \\ \implies \tan A \tan B \tan C & = - \frac pq \\ \implies - \frac qp & = \cot A \cot B \cot C \\ & = \frac {\cos A \cos B \cos C}{\sin A \sin B \sin C} \\ & = \frac {108 - a^2}{bc\cdot ka} \cdot \frac {108 - b^2}{ca\cdot kb} \cdot \frac {108 - c^2}{ab\cdot kc} \\ & = \frac {108^3-108^2(a^2+b^2+c^2)+ 108 (\color{#3D99F6}{(ab)^2 + (bc)^2 +(ca)^2})-(abc)^2}{(abck)^3} & \small \color{#3D99F6}{\text{See Note}} \\ & = - \frac {114192}{13824} = - \frac {793}{96} \end{aligned}

p + q = 96 + 793 = 889 \implies p+q = 96 + 793 = \boxed{889}


Note: \color{#3D99F6}{\text{Note:}}

By Newton's sums (identities) :

a 2 + b 2 + c 2 = ( a + b + c ) 2 2 ( a b + b c + c a ) = 2 4 2 2 ( 180 ) = 216 ( a b ) 2 + ( b c ) 2 + ( c a ) 2 = ( a b + b c + c a ) 2 2 ( a 2 b c + a b 2 c + a b c 2 ) = ( a b + b c + c a ) 2 2 a b c ( a + b + c ) = 18 0 2 2 ( 420 ) ( 24 ) = 12240 \begin{aligned} a^2+b^2+c^2 & = (a+b+c)^2 - 2(ab+bc+ca) \\ & = 24^2 - 2(180) \\ & = \color{#3D99F6}{216} \\ (ab)^2 + (bc)^2 +(ca)^2 & = (ab+bc+ca)^2 - 2(a^2bc+ab^2c+abc^2) \\ & = (ab+bc+ca)^2 - 2abc(a+b+c) \\ & = 180^2 - 2(420)(24) \\ & = \color{#3D99F6}{12240} \end{aligned}

For finding the product of the cosines, we could use the following identity:

c y c sin 2 A = 2 + 2 c y c cos A \sum_{cyc} \sin^2 A = 2 + 2\prod_{cyc} \cos A

A Former Brilliant Member - 4 years, 10 months ago
Mark Hennings
Jul 27, 2016

The polynomial f ( X ) = X 3 24 X 2 + 180 X 420 f(X) = X^3 - 24X^2 + 180X - 420 has roots a , b , c a,b,c . Thus the triangle has semiperimeter s = 12 s = 12 and hence area Δ = s f ( s ) = 12 \Delta = \sqrt{sf(s)} = 12 and hence inradius r = Δ s = 1 r = \tfrac{\Delta}{s} = 1 . Thus tan 1 2 A = r s a = 1 12 a tan 1 2 B = 1 12 b tan 1 2 C = 1 12 c \tan\tfrac12A \; = \; \frac{r}{s-a} \; = \; \frac{1}{12-a} \qquad \tan\tfrac12B \; = \; \frac{1}{12-b} \qquad \tan\tfrac12C \; = \; \frac{1}{12-c} Using the substitution X = 12 Y 1 X = 12 - Y^{-1} , the monic cubic with roots tan 1 2 A \tan\tfrac12A , tan 1 2 B \tan\tfrac12B and tan 1 2 C \tan\tfrac12C is g ( Y ) = Y 3 3 Y 2 + Y 1 12 g(Y) \; = \; Y^3 - 3Y^2 + Y - \tfrac{1}{12} Using the substitution Y = Z Y = \sqrt{Z} , the monic cubic with roots tan 2 1 2 A \tan^2\tfrac12A , tan 2 1 2 B \tan^2\tfrac12B and tan 2 1 2 C \tan^2\tfrac12C is h ( Z ) = Z 3 7 Z 2 + 1 2 Z 1 144 h(Z) \; = \; Z^3 - 7Z^2 + \tfrac12Z - \tfrac{1}{144} Thus tan A + tan B + tan B = tan A tan B tan C = 8 tan 1 2 A tan 1 2 B tan 1 2 C ( 1 tan 2 1 2 A ) ( 1 tan 2 1 2 B ) ( 1 tan 2 1 2 C ) = 8 g ( 0 ) h ( 1 ) = 96 793 \begin{array}{rcl} \tan A + \tan B + \tan B & = & \tan A \tan B \tan C \; =\; \frac{8\tan\frac12A \tan\frac12 B \tan\frac12C}{(1 -\tan^2\frac12A)(1 - \tan^2\frac12B)(1 - \tan^2\frac12C)} \\ & = & -\frac{8g(0)}{h(1)} \; = \; -\frac{96}{793} \end{array} making the answer 96 + 793 = 889 96 + 793 = \boxed{889} .

U s i n g V i e t a s F o r m u l a c y c a = 24 , c y c a b = 180 , a b c = 420. S e m i p e r i m e t e r = s = 1 2 c y c a = 12 A f t e r n o r m a l m a n u p u l a t i o n s , w e g e t c y c a 2 = 216 , a n d c y c a 2 b 2 = 18 0 2 2 420 24 = 12240. Now using Heron’s formula for finding area:- f ( x ) = x 3 24 x 2 + 120 x 420 = ( x a ) ( x b ) ( x c ) [ A B C ] = s f ( s ) = 12 { ( 12 a ) ( 12 b ) ( 12 c ) } f ( 12 ) [ A B C ] = 12 f ( 12 ) = 12 12 = 12 S i n A = 2 [ A B C ] b c = 24 b c , C o s A = 1 S i n 2 A T a n A = 24 b 2 c 2 2 4 2 T a n A + T a n B + T a n C = T a n A T a n B T a n C = 24 b 2 c 2 2 4 2 24 c 2 a 2 2 4 2 24 a 2 b 2 2 4 2 \displaystyle Using Vieta'sFormula\ \ \sum_{cyc}a=24,\ \ \ \ \ \sum_{cyc}ab=180,\ \ \ \ \ abc=420. \\ \displaystyle Semi \ perimeter \ \ =s=\frac 1 2 *\sum_{cyc}a=12\\ After\ normal\ manupulations,\\ \displaystyle we\ get\ \sum_{cyc}a^2=216,\ \ \ \ \ and\ \ \ \ \ \sum_{cyc}a^2b^2=180^2-2*420*24=12240.\\ \text{ Now using Heron's formula for finding area:-}\\ \because\ \ f(x)=x^3-24x^2+120x-420=(x-a)(x-b)(x-c)\\ \therefore\ \ [ABC]=\sqrt{s*f(s)}= \sqrt{12\{\underbrace{(12-a)(12-b)(12-c)\}}_{\color{#3D99F6}{f(12)}}}\\ \therefore\ \ [ABC]=\sqrt{12f(12)}=\sqrt{12\cdot 12}=12\\ SinA=\dfrac {2[ABC]}{bc}=\dfrac {24}{bc},\ \ \ \ \ CosA =\sqrt{1 - Sin^2A}\\ \therefore\ \ TanA =\dfrac{24}{\sqrt{b^2c^2 - 24^2}}\\ TanA+TanB+TanC=TanA*TanB*TanC\\ =\dfrac{24}{\sqrt{b^2c^2 - 24^2}}*\dfrac{24}{\sqrt{c^2a^2 - 24^2}}*\dfrac{24}{\sqrt{a^2b^2 - 24^2}}\\ = 2 4 3 a 4 b 4 c 4 2 4 2 c y c a 2 ( a 2 b 2 c 2 ) + 2 4 4 c y c a 2 b 2 2 4 6 = 2 4 3 42 0 4 2 4 2 216 42 0 2 + 2 4 4 12240 2 4 6 = 96 793 = p q . p + q = 889 \displaystyle =\dfrac{24^3} {\sqrt{ a^4b^4c^4 - 24^2*\sum_{cyc}a^2*(a^2b^2c^2 )+ 24^4*\sum_{cyc}a^2b^2 - 24^6 } } \\ =\dfrac {24^3} {\sqrt{ 420^4 - 24^2*216*420^2+ 24^4*12240 - 24^6 } } \\ =\dfrac {96} {-793} =- \dfrac p q.\\ p+q=\Huge\ \ \ \color{#D61F06}{889}

Note:- Answered required was negative, so on checking one of the angles is 138 degrees, so I have taken negative sign for the square root.

Antonio Antonio
Jul 26, 2016

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...